2007
DOI: 10.1017/s1742170507001779
|View full text |Cite
|
Sign up to set email alerts
|

Feed intake, growth rate and some anatomical characteristics of broilers fed commercial diets supplemented with green feeds

Abstract: A study was conducted on the Teaching and Research Farm of the Rivers State University of Science and Technology, Nigeria to evaluate the nutritional suitability of four treatments, namely a commercial type broiler diet as compared with the commercial diet supplemented with either fresh centrosema (Centrosema molle), pueraria (Pueraria phaseoloides), or waterleaf (Talinium triangulare) leaves. These diets were fed to 120 day-old chicks (Lohmann Brown) over a 62-day period with treatments arranged in a complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Such condition may cause specific micronutrient deficiencies, especially vitamins and minerals, leading to growth retardation in broilers [ 1 ]. To optimize the growth potential of modern broilers in the commercial farms, supplementing the commercial broiler feeds with growth promoters [ 2 ], probiotics [ 3 ], minerals and vitamins [ 4 - 6 ], green foliage/leaf meals [ 7 ], exogenous enzymes [ 8 ], or essential amino acids [ 9 ] has been conducted. With regard to probiotics, vitamins, and minerals, these components have been known to exert an immune-enhancing effect on poultry [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such condition may cause specific micronutrient deficiencies, especially vitamins and minerals, leading to growth retardation in broilers [ 1 ]. To optimize the growth potential of modern broilers in the commercial farms, supplementing the commercial broiler feeds with growth promoters [ 2 ], probiotics [ 3 ], minerals and vitamins [ 4 - 6 ], green foliage/leaf meals [ 7 ], exogenous enzymes [ 8 ], or essential amino acids [ 9 ] has been conducted. With regard to probiotics, vitamins, and minerals, these components have been known to exert an immune-enhancing effect on poultry [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Birds fed KLM had a 0.25% higher GW% than birds on the control diet during the 21 d grow out. Etela et al [25] observed similar outcomes when supplementing green foliage supplements (i.e., fresh centrosema (Centrosema molle), tropical kudzu (Pueraria phaseoloides), or waterleaf leaves (Talinium triangulare)) in broiler diets. The authors concluded that gizzard weight was higher when the diet consisted of supplemented green feeds.…”
Section: Discussionmentioning
confidence: 87%
“…High levels of leaf meals included in the diet could cause nutrient imbalances and inhibit metabolism, thus negatively affecting growth performance [5,48]. However, Etela et al [25] observed that there were no treatment effects on total feed intake and total body weight gain between tropical kudzu and a control diet (commercial type broiler diet) throughout a 62 d grow out. Although traditional feedstuffs (i.e., corn and soybean meal) produce higher performing birds, using kudzu as a protein supplement appears to be a viable option due to birds on KLM still having adequate 21 d average body weight when compared to control and AM in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations